Loving vs. Virginia : A documentary novel of the landmark civil rights case. - Powell, Patricia Hruby; Ojo, Adenrele (Holland : Dreamscape Media, 2017)
In 1955, in Caroline County, Virginia, amidst segregation and prejudice, injustice and cruelty, two teenagers fell in love. Their life together broke the law, but their determination would change it. Richard and Mildred Loving were at the heart of a Supreme Court case that legalized marriage between races, and a story of the devoted couple who faced discrimination, fought it, and won.
Unabridged.
Narrator: Adenrele Ojo.
HL720L
Requires OverDrive Listen (file size: N/A KB) or OverDrive app (file size: 79681 KB).
Young Adult.
Z+
Keywords: Electronic books; Loving, Richard Perry -- Trials, litigation, etc -- Fiction; Loving, Mildred Jeter -- Trials, litigation, etc -- Fiction; Interracial marriage -- Fiction; Race relations -- Fiction; African Americans -- Fiction; Virginia -- History -- Fiction; Historical fiction; SORA Audiobooks